Decoupling of Implied and External VOC Due to Ionic Movement Explaining Transient VOC Overshoot in Perovskite Solar Cells. Issue 2 (1st December 2021) - Herterich, Jan; Unmüssig, Moritz; Wagner, Lukas; Loukeris, Georgios; Faisst, Jared; List, Mathias; Kohlstädt, Markus; Würfel, Uli
Abstract : An overshoot of the open‐circuit voltage ( V OC ) after switching off the illumination is observed for perovskite solar cells, while the simultaneously measured photoluminescence (PL) intensity decreases continuously. Similarly, a dip in the photovoltage transient is detected at the beginning of a light pulse added to a continuous bias light, while the PL increases. This decoupling of external and implied V OC (as derived from the PL data) originates from a strong gradient of the majority charge carrier quasi‐Fermi level in the vicinity of a nonideal contact. This gradient reduces the external voltage much more than the implied voltage. The V OC overshoot is observed whenever the gradient decreases faster than when the separation of the quasi‐Fermi levels is reduced by charge carrier recombination. As shown in previous work, in perovskite solar cells, the magnitude of the gradient is strongly influenced by mobile ionic species and it decreases upon light soaking. This is why a fully light‐soaked device does not show this kind of V OC overshoot. Abstract : The open‐circuit voltage overshoot in perovskite solar cells is investigated by means of photoluminescence/voltage measurements and drift‐diffusion simulations. The overshoot effect originates in the decoupling of the implied and external open‐circuit voltage, which is caused by an ionic space charge in combination with an imperfect contact.